George Washington Paschal, Reporter A Digest of the Laws of Texas: Containing Laws in Force, and the Repealed Laws on Which Rights Rest. Carefully Annotated. 3rd ed. Vol. 2, at 1322, An Act Regulating the Right to Keep and Bear Arms. Art. 6511. (Washington D.C., 1873) - (:unkn) unknown (General Publisher, 1870)
If any person shall go into any church or religious assembly, any school-room or other place where persons are assembled for educational, literary, or scientific purposes, or into a ball room, social party, or other social gathering, composed of ladies and gentleman, or to any election precinct on the day or days of any election, where any portion of the people of this state are collected to vote at any election, or to any other place where people may be assembled to muster or to perform any other public duty, or any other public assembly, and shall have about his person a bowie-knife, dirk, or butcher-knife, or fire-arms, whether known as a six shooter, gun, or pistol of any kind, such person so offending shall be deemed guilty of a misdemeanor, and on conviction thereof shall be fined in a sum not less than fifty or more than five hundred dollars, at the discretion of the court or jury trying the same
--
Keywords: CARRY - CERTAIN PUBLIC PLACES